2021
DOI: 10.1111/jan.14948
|View full text |Cite
|
Sign up to set email alerts
|

‘I wouldn't choose this work again’: Perspectives and experiences of care aides in long‐term residential care

Abstract: Aims To provide insight into the everyday realities facing care aides working in long‐term residential care (LTRC), and how they perceive their role in society. Design A qualitative ethnographic case study. Methods Data were collected over. 10 months of fieldwork at one LTRC setting [September 2015 to June 2016] in Western Canada; semi‐structured interviews (70 h) with 31 care aides; and naturalistic observation (170 h). Data were analysed using reflexive thematic analysis. Results The findings in this work hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 59 publications
2
14
0
Order By: Relevance
“…Bourne and Epstein (2021, 14) observed that having White participants as a majority might create ethnic bias. In a study investigating the experiences of long‐term care aides in Canada, about 83% of participants were White: this was noted by the authors to be an overrepresentation compared to the demographic of workers in this profession (Booi et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bourne and Epstein (2021, 14) observed that having White participants as a majority might create ethnic bias. In a study investigating the experiences of long‐term care aides in Canada, about 83% of participants were White: this was noted by the authors to be an overrepresentation compared to the demographic of workers in this profession (Booi et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Gendered power relations in the experience of moral distress were noted to also emanate from interactions with other health care professionals such as male physicians (Addo et al., 2020; Biondi et al., 2019; Boakye et al., 2021; Booi et al., 2021; Langley et al., 2015). One study noted that care aides in British Columbia, Canada, are typically female, over the age of 40 with English as their second language: “The gendered notions of unskilled work, body care and stigma related to this work and the corresponding maltreatment of this workforce is a continuation of the narrative of unvalued predominantly female roles in society” (Booi et al., 2021, p. 13). These studies situate moral distress within the broader context of gender norms which influence how healthcare work is valued and resourced.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the increased prevalence, risks and consequences of inadequate food intake, residents are not always provided with optimal mealtime care (Hammar et al, 2016; Lea et al, 2017). Direct care staff, who remain an unsupported and unprepared workforce that is critical to quality care (Booi et al, 2021), report a need for training on the use of resident ‐ and relationship ‐ centred , individualised care approaches integrating management of fluctuating mealtime challenging behaviours to achieve optimal care while minimising risks of inadequate food intake through building relational and emotional connections (Douglas et al, 2021; Li et al, 2021). Effective , multi‐level interventions that optimise mealtime care quality warrant fundamental components , including supportive organisational systems , foundational and interprofessional person‐centred cultures , and adequate staff training ( Brunner et al, 2021; Fazio et al, 2020; Villar et al, 2021).…”
Section: Relevance To Clinical Practicementioning
confidence: 99%
“…Likewise, aged-care workers may feel greater job dissatisfaction when they accept negative perceptions about their job (Manchha et al, 2021). This psychological distress and job dissatisfaction may also be reflected in greater turnover intention (i.e., intentions to leave their job; Booi et al, 2021). Gao and colleagues (2015) found nursing assistants were more determined to leave aged care when they felt “less than.” Thus, we predict that workers who have internalized the stigma of their work may experience greater psychological distress, job dissatisfaction, and turnover intentions.…”
Section: Direct Effects Of Internalized Stigma On Aged-care Workers O...mentioning
confidence: 99%